Electroosmosis Augmented MHD Peristaltic Transport of SWCNTs Suspension in A Porous Media - Lafta, Hana Ibrahim; Abdulhadi, Ahmed M.; Thawi, Mizal Hamad (Iraqi Journal of Science, 2024)
In this article, we analyses electroosmosis augmented MHD peristaltic transport of SWCNTs suspension in porous media, the basic equations have been constructed under assumptions of low Reynolds number and long wave length. The exact solution by the regular perturbation technique are obtained and the flow qualities have been plotting by using MATHEMATICA software for all the figures. Series solution for stream function, pressure gradient and temperature distribution have been computed in the peristaltic transport in an asymmetric channel